Ping-pong Asylum: Renegotiating the Safe Third Country Agreement - Robert Falconer (The School of Public Policy Publications, 2019)
Asylum seekers crossing the U.S. border into Canada deserve to have their claims dealt with in a timely manner. To accomplish this, Canada should dedicate more resources to processing claims, rather than finding new ways to force these people back into the U.S. by renegotiating the Safe Third Country Agreement (STCA) between the two countries. During the two years leading up to February 2019, the RCMP intercepted some 42,000 asylum seekers at the border, which amounted to one-third of all asylum claims in that time. Another 70,800 asylum claimants arrived at official ports of entry or applied for asylum from inside Canada. The STCA permits Canada to return asylum seekers to the U.S. if they first arrived in that country, and vice-versa. However, the STCA applies only to official ports of entry and not to asylum seekers that cross the border illegally. American sentiment at the time the pact was signed held that border officials could only be accountable for areas where they were physically present. However, this gives asylum seekers an incentive to avoid crossing at ports of entry. Clearly, it is impossible to staff every kilometre of the border between the two countries. But renegotiating the STCA to give officials the power to return to the U.S. all asylum seekers crossing the border at any point, is not the solution. The legalities of such an amendment, including its constitutionality, are murky and there are non-legal pros and cons involved with renegotiating the pact. There is already a sizable backlog of asylum claims from people who cross at ports of entry. Returning those who cross elsewhere to the U.S. would ease this caseload, and these claimants would still get a fair refugee hearing in the U.S. However, expanding the treaty to include all asylum seekers, regardless of how they enter Canada, may deter those with legitimate claims who are applying for refugee status through regular means at ports of entry or from inside Canada as students or tourists. Amending the STCA could serve to deter asylum seekers with trivial claims, but people afraid of being turned back to the U.S. might also resort to evasive and riskier measures. They might choose more isolated routes to cross the border and then live for long periods of time illegally in Canada. It would be far better to hire more personnel and invest in other resources to speed up the overall claims process. This would reduce both the backlog and the potential for new border crossings. When wait times for processing are long, asylum seekers may decide the chance to work, and the opportunity to receive health care and social assistance, are worth the risk of being rejected farther down the line. Border crossings by asylum seekers have dropped significantly in the past two years. Reducing claim processing times instead of amending the STCA means saving money that might otherwise be spent on providing health care and social assistance to claimants taking their chances on a lengthy process to live here illegally. When processing times are speeded up, legitimate refugees would be dealt with more quickly and those with dubious claims would think twice about crossing illegally. Canada’s debate on border security should focus, not on a solution mired in more legalities, but on creating efficient and effective bureaucratic responses to processing asylum claims.